A dual-purpose vibration isolator energy harvester: Experiment and model. (1st March 2019) - Mofidian, S.M. Mahdi; Bardaweel, Hamzeh
Highlights: A dual purpose device is fabricated, modeled, and characterized. The device features elastic and magnetic springs to facilitate its dual functionality. The device isolates the mass and converts vibrations into useful electric energy. The device attenuates vibrations higher than 12.5 Hz and recovers 0.115 mW. Abstract: A new dual-purpose vibration isolator energy harvester device suitable for low frequency operation is presented in this work. The device features a combination of elastic and magnetic components to facilitate its dual functionality. The main purpose of the dual-purpose device is preventing vibrations from traveling through the isolated mass using magnetic and viscous dampers and elastic and magnetic springs. A secondary task is converting some of the kinetic energy contained in these oscillations into useful electric energy. Numerical and analytical models are developed and used to simulate the behavior of the device. The models are validated against measured data. Experiments demonstrate the ability of the device to, simultaneously, isolate the desired mass and harvest energy from unwanted free vibrations. The dual-purpose device attenuates oscillations higher than 12.5 [Hz] while, simultaneously, recovers 0.115 [mW] at 9.81 m.s −2 . The power produced by the dual-purpose device is significantly higher than the power recovered by its rival regenerative devices reported in literature. Moreover, results from model parametric study and experimental data show that the combined positive and negative stiffness elements in this device hold the promise for lower operating frequencies and higher output power. Initial results suggest that lowering the linear stiffness of the device can potentially lower the cut-off frequency to approximately 9 [Hz] while generating 1 [mW] electric power.